Comparison Between State and Private University Student of Adversity Quotient on Online Learning - Mardiana, Dina; Umiarso, Umiarso (Institute Of Advanced Knowledge and Science, 2025)
This study intends to investigate how Adversity Quotient (AQ) or Intelligence in Facing Student Obstacles might be formed through online learning at PTKIs, the Private University in Malang and the Universitas Muhammadiyah Malang. The COVID-19 epidemic, which compelled universities to adapt to online learning, caused alterations in learning patterns at PTKI, which served as the foundation for this study. The study aimed to explore the Adversity Quotient among students, focusing on four core dimensions: Control, Ownership, Reach, and Endurance. Additionally, the study examined four dimensions pertinent to online learning: Student Performance, Technology, Lecturer, and Self-Regulation. As a result, it is clear that the responders at the State University of Malang have performed admirably, are able to overcome obstacles, and are able to maximize the potential that rises daily. In contrast to the low scores of University